Nilai Perusahaan: Hubungan Keputusan Investasi, Keputusan Pendanaan Dan Kebijakan Dividen Perusahaan Jasa - Nur Syamsu; Anwar Anwar (AkMen JURNAL ILMIAH, 2021)
The purpose of this research is to examine the relationship between firm value using investment decisions, funding decisions and dividend policies. The data used is data from trading sector service companies obtained from the Indonesia Stock Exchange for the 2018 period from the https://https://id website and by browsing the websites of companies that open company reports. The population in this study are all service sector companies listed on the Indonesia Stock Exchange in 2018 totaling 420 service companies with purposive sampling technique so that the total sample is financial data from 103 service companies listed on the Indonesia Stock Exchange in 2018. The analytical tool used is analysis. multiple linearity with SEM-PLS. Partial Least Square (PLS). The results of the study found that investment decisions have a significant effect on firm value. Meanwhile, the source decision and dividend decision have no effect on firm value.